2004
DOI: 10.1291/hypres.27.865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bradykinin on Cardiovascular Remodeling in Renovascular Hypertensive Rats

Abstract: Angiotensin converting enzyme (ACE) inhibitors inhibit both the formation of angiotensin II and the catabolism of bradykinin (BK).sion of angiotensin I into angiotensin II (ATII). ACE inhibitors block not only ATII formation but also bradykinin (BK) degradation. Some pharmacological effects of ACE inhibitors are mediated by endogenous preservation of BK. BK is a potent vasodilator peptide, which possesses cardioprotective action via BK B2 receptor. The binding of BK to B2 receptor activates second messengers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, massive fibrosis of the RV wall, characteristic of right ventricular dysplasia, was not observed in NEPAS/HIF-3␣ Ϫ/Ϫ hearts. Furthermore, the expression of brain natriuretic peptide mRNA, known to be elevated in cardiomyopathy (32), was normal in the mutant RV (data not shown). Hence, the available lines of evidence do not support the contention that cardiomyopathy is the cause of RV enlargement in NEPAS/HIF-3␣ Ϫ/Ϫ mice.…”
Section: [N ϭ 8]) and Nepas/hif-3␣mentioning
confidence: 91%
“…However, massive fibrosis of the RV wall, characteristic of right ventricular dysplasia, was not observed in NEPAS/HIF-3␣ Ϫ/Ϫ hearts. Furthermore, the expression of brain natriuretic peptide mRNA, known to be elevated in cardiomyopathy (32), was normal in the mutant RV (data not shown). Hence, the available lines of evidence do not support the contention that cardiomyopathy is the cause of RV enlargement in NEPAS/HIF-3␣ Ϫ/Ϫ mice.…”
Section: [N ϭ 8]) and Nepas/hif-3␣mentioning
confidence: 91%
“…In dogs, detailed analyses have revealed that the RAS existing in cardiac tissue has a crucial role in the development of hypertrophy [2]. Cardiac ACE plays a role not only in generating Ang II, which provokes cardiac hypertrophy and fibrosis through Ang II type 1 (AT1) receptor signaling [4,12,23], but also in increasing cardiac fibrosis by catalyzing the degradation of bradykinin into inactive metabolites [3,9,26,30]. Similarly, cardiac chymase plays a role not only in converting Ang I to Ang II [31], but also in promoting direct collagen production [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The methods have been described in detail in 2 previous reports. 11,16) The main procedures used in the present study were as follows. RHT rats were produced by constricting the left renal artery with a silver clip (two-kidney one-clip: 2K1C) in male Wistar rats weighing 130 to 150 g. One week after the operation, rats with a systolic blood pressure (SBP) of over 140 mmHg were considered as representing the RHT model.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the degree of myocardial fibrosis, photomicrographic figures of the sections were digitized and the fibrotic areas were assigned numerical values using NIH image software. 16) Vascular tissue changes were evaluated according to the method described by Ito, et al…”
Section: Methodsmentioning
confidence: 99%